2014
DOI: 10.1007/s00296-014-3173-1
|View full text |Cite
|
Sign up to set email alerts
|

A case of PRES in an active lupus nephritis patient after treatment of corticosteroid and cyclophosphamide

Abstract: Posterior reversible encephalopathy syndrome (PRES) is primarily a radiological diagnosis. The syndrome is characterized by headache, altered mental status, seizures, and bilateral posterior white matter edema in a nonvascular distribution on neuroimaging with resolution of findings usually in 7-14 days (Casey et al. in AJNR Am J Neuroradiol 21:1199-1206, 2000). In most cases, computed tomography of the brain will show hypodense lesions in the parieto-occipital lobe. Although this syndrome is uncommon, prompt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Chang-Hoon Lee reported a case of a 42-year-old woman with systemic lupus erythematosus (SLE) who presented with renal failure secondary to glomerulonephritis and developed PRES after two cycles of cyclophosphamide [30]. Jabrane et al reported a case of a 16-year-old girl with SLE and lupus nephritis who presented with renal failure and developed sudden onset of a headache, blurring of vision, followed by three episodes of generalized seizures after being treated with IV cyclophosphamide pulse therapy at 300 mg/m 2 of the body surface [28]. Zekić et al reported a case of an 18-year-old girl with of SLE who presented with renal failure due to lupus nephritis and acute arthritis and developed PRES after administration of the second dose of cyclophosphamide [25].…”
Section: Discussionmentioning
confidence: 99%
“…Chang-Hoon Lee reported a case of a 42-year-old woman with systemic lupus erythematosus (SLE) who presented with renal failure secondary to glomerulonephritis and developed PRES after two cycles of cyclophosphamide [30]. Jabrane et al reported a case of a 16-year-old girl with SLE and lupus nephritis who presented with renal failure and developed sudden onset of a headache, blurring of vision, followed by three episodes of generalized seizures after being treated with IV cyclophosphamide pulse therapy at 300 mg/m 2 of the body surface [28]. Zekić et al reported a case of an 18-year-old girl with of SLE who presented with renal failure due to lupus nephritis and acute arthritis and developed PRES after administration of the second dose of cyclophosphamide [25].…”
Section: Discussionmentioning
confidence: 99%
“…A lumbar puncture could be useful to eliminate meningitis, or a malignant cause. However, cerebrospinal fluid in PRES often only shows moderately elevated protein levels with less than 5 leucocytes/µl [12] . Differential diagnosis for PRES in a patient with a pre-established diagnosis of SLED, includes lupus cerebritis, neuropsychiatric-lupus, meningitis, ischemia, hemorrhage, a primary seizure disorder and many others, and PRES should be considered an elimination diagnosis with supportive findings.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of PRES remains symptomatic and etiological, and consists of rapid maintain of blood pressure and neuro-reanimation to avoid permanent damage. Patients presenting with PRES who are also on immunosuppressive therapy should have their medication temporarily discontinued or a decrease in dosage until the patient improves [12] . The prognosis in usually favorable in the classic form of PRES, as there is complete regression of the clinical and radiological signs once the underlying cause is managed promptly, nevertheless this reversible outcome is not always found.…”
Section: Discussionmentioning
confidence: 99%
“…It took longer to develop PRES with oral cyclophosphamide compared to IV drugs. Furthermore, two patients with ANCA-associated vasculitis and one with lupus nephritis who used IV injection developed PRES in 3 d[ 5 , 6 , 11 ]. Among two cases of oral cyclophosphamide-induced PRES, Cha et al [ 7 ] reported a 36-year-old woman with anti-GBM Ab glomerulonephritis treated with oral methylprednisolone, plasmapheresis and oral cyclophosphamide who suddenly developed PRES after 3 mo of treatment.…”
Section: Discussionmentioning
confidence: 99%